A novel synthesis route for brookite rich titanium dioxide photocatalyst involving organic intermediate - Manjumol, K.; Jayasankar, M.; Vidya, K.; Mohamed, A.; Nair, Balagopal; Warrier, K. (2014)
© 2014, Springer Science+Business Media New York.High temperature stable brookite rich titanium dioxide of average crystallite size 20 nm has been prepared by a novel aqueous sol–gel method involving hydroxyethyl cellulose polymer (HEC) as an organic intermediate, wherein titania powder with brookite phase content as high as 44 wt% was obtained. The existence of brookite phase has been evident even after calcination of the samples at 900 °C, which also helped to maintain a specific surface area value of 5.5 m2g-1 compared to the surface area of 2.2 m2g-1 measured on pure titania sample with only rutile phase. The brookite rich titania exhibited superior photocatalytic activity under UV irradiation with a rate constant value of 0.011 min-1 compared to the value of 0.003 min-1 measured for pure rutile phase rich titania samples under similar conditions. The present study indicates that HEC assisted thermal decomposition can be an effective route to produce efficient photoactive brookite rich titania powders.